2007
DOI: 10.1002/14651858.cd002187.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase inhibitors for erectile dysfunction in patients with diabetes mellitus

Abstract: Background Erectile dysfunction is a common multi-factorial complication of diabetes mellitus. Numerous strategies have been tried to overcome this diabetic complication. In recent years, phosphodiesterase type 5 (PDE-5) inhibitors have been introduced in the management of erectile dysfunction. Objectives The objective of this review was to assess the effect of PDE-5 inhibitors on the management of erectile dysfunction in diabetic men. Search methods Studies were obtained from computerised searches of MEDLINE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…These drugs differ in their time to onset and in their duration of action, but they show the same efficacy and safety profile. All of them have shown their efficacy in diabetic patients,84 although it has been reported that diabetic men with ED are less responsive to PDE5 inhibitors when compared with nondiabetic men with ED 85. A randomized, placebo controlled trial, involving 268 diabetic men with ED, reported improved erections in 56% of patients taking sildenafil in a dose-dependent manner, compared with 10% of those in the control group 86.…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
“…These drugs differ in their time to onset and in their duration of action, but they show the same efficacy and safety profile. All of them have shown their efficacy in diabetic patients,84 although it has been reported that diabetic men with ED are less responsive to PDE5 inhibitors when compared with nondiabetic men with ED 85. A randomized, placebo controlled trial, involving 268 diabetic men with ED, reported improved erections in 56% of patients taking sildenafil in a dose-dependent manner, compared with 10% of those in the control group 86.…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
“…All of them have shown their efficacy in diabetic patients 100. The three drugs differ from each other in time to onset and duration of action, but have similar efficacy and safety profiles.…”
Section: Treatmentmentioning
confidence: 99%
“…2 Approximately 50% of diabetics may eventually develop nerve damage. 3 Moreover, depending on affected nerves, symptoms of DN can range from pain and numbness in extremities to digestive system, urinary tract, blood vessels, and heart problems. 4 Pathogenic mechanisms linking hyperglycemia with DN include increased polyol pathway flux, protein kinase C activation, increased hexosamine pathway flux, enhanced formation of reactive oxygen species, increased production of vascular endothelial growth factor, and altered generation of endothelial nitric oxide (NO).…”
mentioning
confidence: 99%